2004
DOI: 10.1016/j.femsec.2004.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and biodiversity of 2,4-diacetylphloroglucinol-producing rhizobacteria are differentially affected by the genotype of two maize inbred lines and their hybrid

Abstract: Rhizobacteria (2808) were isolated on Pseudomonas-selective S1 medium from two maize inbred lines and from their hybrid at three plant growth stages. Positive phl D hybridization was found for 364 of them. The PhlD+ isolates were significantly more numerous in the rhizosphere of the hyrid than in those of parental lines. Furthermore, the frequency of PhlD+ was significantly higher for the hybrid at the flowering stage. An amplified rDNA restriction analysis showed that the hybrid genotype also increases the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 44 publications
4
43
0
Order By: Relevance
“…A major challenge in screening for enhanced microbial rootcolonization is the design of effective procedures that provide a reproducible classification in the field environment. Level of root colonization exhibits dramatic variation related to plant age (Picard et al 2000(Picard et al , 2004Roesh et al 2006), thus genotype rank can vary significantly depending upon plant age at the time of analysis. For example, the frequency of beneficial root-colonizing microorganisms was found to be very low in the initial stage of plant growth, greatly increased at the flowering stage, and then decreased with physiological maturation, at least for maize (Picard et al 2000, Roesh et al 2006 and for Achillea ageratum L plants (Picard and Bosco 2003).…”
Section: Useful Traits For Better Nutrition Via Beneficial Plant-micrmentioning
confidence: 99%
“…A major challenge in screening for enhanced microbial rootcolonization is the design of effective procedures that provide a reproducible classification in the field environment. Level of root colonization exhibits dramatic variation related to plant age (Picard et al 2000(Picard et al , 2004Roesh et al 2006), thus genotype rank can vary significantly depending upon plant age at the time of analysis. For example, the frequency of beneficial root-colonizing microorganisms was found to be very low in the initial stage of plant growth, greatly increased at the flowering stage, and then decreased with physiological maturation, at least for maize (Picard et al 2000, Roesh et al 2006 and for Achillea ageratum L plants (Picard and Bosco 2003).…”
Section: Useful Traits For Better Nutrition Via Beneficial Plant-micrmentioning
confidence: 99%
“…Chasselas was grafted, which might also have influenced results. Morano and Kliewer (1994) showed that root growth and activity may vary according to grapevine cultivar or rootstock, and the diversity of rhizosphere bacteria can differ when comparing different plant cultivars (Okubara et al, 2004;Picard et al, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…To compare climatic conditions without altering soil parameters, Picard et al (2004a) performed two trials on maize, sown 3 weeks apart in the same field. DAPG producers were isolated from maize rhizospheres sampled at the same physiological stages.…”
Section: Geographic Location and Climatementioning
confidence: 99%
“…Unfortunately, no similar research was done specifically on PFP populations. However, by comparing DAPG pseudomonads populations isolated from hybrid maizes and from their respective linear parental ones, it was suggested that root colonization by this type of rhizobacteria is an inherited trait, probably related to heterosis (Picard et al 2004a;Picard and Bosco 2006). In fact, repeated experiments in the field give evidence that maize hybrids are colonized more by DAPG-producing Pseudomonas strains characterized by an efficient disease suppression potential than parental lines.…”
Section: Genotypes Within the Same Plant Speciesmentioning
confidence: 99%
See 1 more Smart Citation